Reksa Pastoral Care Elaborasi Pendekatan Holistik bagi Pendampingan Lanjut Usia - Martinus Irwan Yulius (Forum, 2023)
One of the church's attention and concern in pastoral work is pastoral care. Pastoral care becomes an integral part of the church's mission in proclaiming God's work of salvation. Pastoral care within the framework of caring for the souls of the faithful is carried out in different contexts based on the age, situation, and needs of the people. One of the works that the church has been engaged in is pastoral care for the elderly people. These elderly people have different and special characters, situations and needs. The purpose of this research is how to pay attention to all dimensions of life (biopsychosociospiritual) in assisting the elderly. The research method used in this research is literature study; This elaboration will be complemented by data and facts taken from existing studies on this area of study. The results of this study show several practical steps that can be taken to provide integral assistance to elderly people.